Improvements of tooth movement efficiency and torque control in expanding the arch with clear aligners: a finite element analysis - Yao, Song; Jiang, Wei; Wang, Chunjuan; He, Yao; Wang, Chao; Huang, Lan (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives： The purpose of this study was to analyze the effect of different movement strategies, embossment structures, and torque compensation of the aligner on tooth movement during arch expansion using clear aligners by the finite element analysis. Methods: Models comprising the maxilla, dentition, periodontal ligament, and aligners were created and imported into a finite element analysis software. The tests were performed using the following: three tooth movement strategies (including alternating movement with the second premolar and first molar, whole movement with first premolar and first molar or premolars and first molar), four different shapes of embossment structures (ball, double ball, cuboid, cylinder, with 0.05-mm, 0.1-mm, 0.15-mm interference) and torque compensation (0°, 1°, 2°, 3°, 4°, and 5°). Results: Clear aligner expanding the arch caused the target tooth to move obliquely. Alternating movement resulted in higher movement efficiency with lower anchorage loss as compared with whole movement. Embossment increased the efficiency of crown movement but did not contribute positively to torque control. As the angle of compensation increased, the tendency of oblique tooth movement was gradually controlled; however, the movement efficiency decreased concurrently, and stress distribution on the periodontal ligament became more even. For each 1° increase in compensation, the torque per millimeter of the first premolar decreased by 0.26°/mm, and the crown movement efficiency decreased by 4.32%. Conclusion: Alternating movement increases the efficiency of the arch expansion by the aligner and reduces anchorage loss. Torque compensation should be designed to enhance torque control in arch expansion using an aligner.